Long‐Lasting Efficacy of Coatings for Bronze Artwork Conservation: The Key Role of Layered Double Hydroxide Nanocarriers in Protecting Corrosion Inhibitors from Photodegradation. (3rd May 2018) - Salzano de Luna, Martina; Buonocore, Giovanna G.; Giuliani, Chiara; Messina, Elena; Di Carlo, Gabriella; Lavorgna, Marino; Ambrosio, Luigi; Ingo, Gabriel M.
Abstract: The photodegradation kinetics of 2‐mercaptobenzothiazole (MBT), a corrosion inhibitor for copper‐based alloys, is studied in high amorphous polyvinyl alcohol coatings subjected to either UV irradiation or indoor light exposure. The photodegradation process proceeds rapidly, thus compromising the anticorrosion ability of the coating. The encapsulation of MBT into layered double hydroxide (LDH) nanocarriers slows down its decomposition kinetics by a factor of three. Besides preserving the corrosion inhibitor, such a strategy allows a controlled release of MBT triggered by corrosion‐related stimuli, for example, presence of chloride species and acid pH. The developed coating guarantees long‐lasting corrosion protection even at low amounts of inhibitor‐loaded LDH nanocarriers (ca. 5 wt %). This also reflects in a high transparency, which makes the protective coating suitable for demanding applications, such as the conservation of high‐value metal works of art.